A Photoswitchable Agonist for the Histamine H3 Receptor, a Prototypic Family A G‐Protein‐Coupled Receptor. Issue 14 (27th February 2019) - Hauwert, Niels J.; Mocking, Tamara A. M.; Da Costa Pereira, Daniel; Lion, Ken; Huppelschoten, Yara; Vischer, Henry F.; De Esch, Iwan J. P.; Wijtmans, Maikel; Leurs, Rob
Abstract: Spatiotemporal control over biochemical signaling processes involving G protein‐coupled receptors (GPCRs) is highly desired for dissecting their complex intracellular signaling. We developed sixteen photoswitchable ligands for the human histamine H3 receptor (hH3 R). Upon illumination, key compound 65 decreases its affinity for the hH3 R by 8.5‐fold and its potency in hH3 R‐mediated Gi protein activation by over 20‐fold, with the trans and cis isomer both acting as full agonist. In real‐time two‐electrode voltage clamp experiments in Xenopus oocytes, 65 shows rapid light‐induced modulation of hH3 R activity. Ligand 65 shows good binding selectivity amongst the histamine receptor subfamily and has good photolytic stability. In all, 65 (VUF15000) is the first photoswitchable GPCR agonist confirmed to be modulated through its affinity and potency upon photoswitching while maintaining its intrinsic activity, rendering it a new chemical biology tool for spatiotemporal control of GPCR activation. Abstract : Shedding light on G‐protein‐coupled receptor activation : VUF15000 is a photoswitchable histamine H3 receptor agonist showing full Gi protein activation in both its trans and cis isomer. Moreover, it shows dynamic optical H3 receptor modulation in electrophysiology experiments. VUF15000 can serve as a valuable photochromic tool compound for unraveling the H3 receptor signaling cascade with spatiotemporal precision.